Overexpression of OsTF1L, a rice HD‐Zip transcription factor, promotes lignin biosynthesis and stomatal closure that improves drought tolerance - Bang, Seung Woon (Plant Biotechnol J, 2018)
Drought stress seriously impacts on plant development and productivity. Improvement of drought tolerance without yield penalty is a great challenge in crop biotechnology. Here, we report that the rice (Oryza sativa) homeodomain‐leucine zipper transcription factor gene, OsTF1L (Oryza sativa transcription factor 1‐like), is a key regulator of drought tolerance mechanisms. Overexpression of the OsTF1L in rice significantly increased drought tolerance at the vegetative stages of growth and promoted both effective photosynthesis and a reduction in the water loss rate under drought conditions. Importantly, the OsTF1L overexpressing plants showed a higher drought tolerance at the reproductive stage of growth with a higher grain yield than nontransgenic controls under field‐drought conditions. Genomewide analysis of OsTF1L overexpression plants revealed up‐regulation of drought‐inducible, stomatal movement and lignin biosynthetic genes. Overexpression of OsTF1L promoted accumulation of lignin in shoots, whereas the RNAi lines showed opposite patterns of lignin accumulation. OsTF1L is mainly expressed in outer cell layers including the epidermis, and the vasculature of the shoots, which coincides with areas of lignification. In addition, OsTF1L overexpression enhances stomatal closure under drought conditions resulted in drought tolerance. More importantly, OsTF1L directly bound to the promoters of lignin biosynthesis and drought‐related genes involving poxN/PRX38, Nodulin protein, DHHC4, CASPL5B1 and AAA‐type ATPase. Collectively, our results provide a new insight into the role of OsTF1L in enhancing drought tolerance through lignin biosynthesis and stomatal closure in rice.